2018
DOI: 10.1038/s41598-018-27850-y
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Omega-3 docosahexaenoic acid induces pyroptosis cell death in triple-negative breast cancer cells

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Pyroptosis is a new cell death mediated by proteases activated within inflammasomes. It is also a prominent target to mediate anti-tumour treatments [24]. In ALA loaded lipid/ PLGA MBs mediated SDT, we also observed pyroptosis in AsPC-1 and BxPC-3 cells.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Pyroptosis is a new cell death mediated by proteases activated within inflammasomes. It is also a prominent target to mediate anti-tumour treatments [24]. In ALA loaded lipid/ PLGA MBs mediated SDT, we also observed pyroptosis in AsPC-1 and BxPC-3 cells.…”
Section: Discussionsupporting
confidence: 52%
“…In ALA loaded lipid/ PLGA MBs mediated SDT, we also observed pyroptosis in AsPC-1 and BxPC-3 cells. Pore formation in cell membrane is the most important event in pyroptosis [24]. In the ALA loaded lipid/PLGA MBs mediated SDT group, the MBs destruction and cavitation may take part in the membrane pore formation in pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…9). Subsequently, an increasing number of chemical target drugs, reagents, and natural products have been found to cause pyroptosis in various types of cancers, many of which imbue antitumor effects [234][235][236][237][238][239][240][241] (Table 2).…”
Section: Chemotherapymentioning
confidence: 99%
“…Recent studies have revealed the roles of pyroptosis in several types of cancers, including colon cancer, gastric cancer, lung cancer, breast cancer, liver cancer, and glioma. However, no studies have focused on the pyroptosis in PDAC (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%